New genre of antioxidants from renewable natural resources: Synthesis and characterisation of rosemary plant-derived antioxidants and their performance in polyolefins. (August 2016) - Doudin, K.; Al-Malaika, S.; Sheena, H.H.; Tverezovskiy, V.; Fowler, P.
Abstract: Several ester derivatives of rosmarinic acid (rosmarinates) were synthesised, characterised (1D and 2D NMR, UV and FTIR spectroscopy) and tested for their potential use as antioxidants derived from a renewable natural resource. The intrinsic free radical scavenging activity of the rosmarinates was assessed, initially using a modified DPPH (2, 2-diphenyl-1-picrylhydrazyl radical) method, and found to be higher than that of commercial synthetic hindered phenol antioxidants Irganox 1076 and Irganox 1010. The thermal stabilising performance of the rosmarinates in polyethylene (PE) and polypropylene (PP) was subsequently examined and compared to that of samples prepared similarly but in the presence of Irganox 1076 (in PE) and Irganox 1010 (in PP) which are typically used for polyolefin stabilisation in industrial practice. The melt stability and the long-term thermo-oxidative stability (LTTS) of processed polymers containing the antioxidants were assessed by measuring the melt flow index (MFI), melt viscosity, oxidation induction time (OIT) and long-term (accelerated) thermal ageing performance. The results show that both the melt and the thermo-oxidative stabilisation afforded by the rosmarinates, and in particular the stearyl derivative, in both PE and PP, are superior to those of Irganox 1076 and Irganox 1010, hence their potential as effective sustainable bio-based antioxidants for polymers. The rosmarinic acid used for the synthesis of the rosmarinates esters in this study was obtained from commercial rosemary extracts (AquaROX80). Furthermore, a large number of different strains of UK-grown rosemary plants (Rosmarinum officinalis) were also extracted and analysed in order to examine their antioxidant content. It was found that the carnosic and the rosmarinic acids, and to a much lesser extent the carnosol, constituted the main antioxidant components of the UK-plants, with the two acids being present at a ratio of 3:1, respectively.